La recherche en sciences sociales dans les écoles de paysage en France - Monique Toublanc (Projets de Paysage)
The investigation on landscape as object of research through social sciences has been, during a long time, mainly conducted by research institutions and Universities. The landscape schools, developed recently, have finally taken over this issue, but in a specific way : by raising no more the landscape but the project of landscape as object of research, even as process of research. This approach is claimed by the professionals of landscape and constitutes a hotbed for the development of a new theoretical field for researchers in social sciences and landscape architects. However, even if it seems legitimate to attempt to understand the project of landscape which could be compared to a « black box», it seems necessary to continue and enhance the research on landscape, notably in social sciences, particularly during a period in which all part of territory à exceptional or ordinary – has become landscape.